A DELIBERATION ON SOME IMPORTANT ASPECTS OF VALUES AND THE PARADOX OF PRESENT DAY - Roslan Abd Jelani (Sekolah Tinggi Agama Islam Indonesia Jakarta, 2018)
In Islamic value system, the individual is not considered as a mechanical tool in the social system. Rather, it gives to each – the individual and society – their rights accordingly. Through this system, a person is able to evaluate all his actions based on the truth of Revelation. He will know that not everything dictated by personal interest is permissible. This research will argue that moral dynamism can’t be achieved until all the systems that deemed to fit the worldview of Islam can be harmonized based upon the experience of gaining and realizing the reality and truth. The righteous person is the one who, in his various capacities, moves by the guidance of Revelation, hence achieve the glorified success (al-falah) and real happiness (al-sa’adah).